2017
DOI: 10.2174/1568009616666161208150148
|View full text |Cite
|
Sign up to set email alerts
|

New Candidate Genes for Lack of Sensitivity to Therapy in Pediatric Leukemias

Abstract: In the recent years, significant development of molecular genetics has contributed to the better understanding of leukemogenesis and classification of the different leukemia subtypes. Patients diagnosed with acute leukemia usually undergo chemotherapy, which involves the induction of remission, consolidation of remission and maintenance therapy. Patients are still vulnerable to relapse due to differences in the sensitivity of leukemia cells to the chemotherapeutic agent, because of the active drugs removal fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, many recent studies in acute leukemia cases have shown that miR‐128b is significantly overexpressed in pediatric ALL cases at diagnosis than controls and in ALL cases more than in AML cases 27‐30 . In addition, in vitro studies performed have shown miR‐128b to be involved in development of drug resistance to vincristine and prednisolone, pointing toward a possible mechanism for disease relapse in ALL 31 . miR‐378c is a tumor suppressive miRNA and studies have shown it to be downregulated in cancers especially bladder and colon cancers and its down‐regulation leads to tumor metastasis and poor outcome 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…However, many recent studies in acute leukemia cases have shown that miR‐128b is significantly overexpressed in pediatric ALL cases at diagnosis than controls and in ALL cases more than in AML cases 27‐30 . In addition, in vitro studies performed have shown miR‐128b to be involved in development of drug resistance to vincristine and prednisolone, pointing toward a possible mechanism for disease relapse in ALL 31 . miR‐378c is a tumor suppressive miRNA and studies have shown it to be downregulated in cancers especially bladder and colon cancers and its down‐regulation leads to tumor metastasis and poor outcome 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding MDR, NGS technologies allow us to identify DNA-and RNA-based molecular profiles associated with tumor development, progression and therapy outcome and thus recognize genetic determinants of MDR phenomenon in solid tumors (Chandana et al, 2019;Gov et al, 2017;Kyrochristos et al, 2019;Verma and Sharma, 2018) and leukemia (Albitar et al, 2017;Bereza et al, 2017;Szankasi et al, 2016). On the basis of ultra-deep sequencing, it is also possible to understand and combat the antibiotic resistome (Crofts et al, 2017;Hadjadj et al, 2019) and characterize in detail, drug resistance-associated mutations in pathogens and viruses causing serious diseases (Alidjinou et al, 2017;Gautam et al, 2019;Parker and Chen, 2017;Ramanathan et al, 2017;Soares et al, 2019;Thomson et al, 2016) as summarized in Fig.…”
Section: Next-generation Sequencing (Ngs) In Cancer Mdr Researchmentioning
confidence: 99%
“…A study published in 2015 by Hamzeh et al showed that miRNA-related dysregulated pathways were associated to resistance to asparaginase (L_ASP), daunorubicin (DAUNO), prednisolone (PREDS), and vincristine (VIN) [ 36 ]. Several miRNAs have been attributed an association with leukemia treatment resistance, such as miR-34 [ 37 , 38 ], miR-128b, and miR-223 [ 39 ]. Zhang et al [ 23 ] described an miRNA signature (miR-18a, miR-532, miR-218, miR-625, miR-193a, miR-638, miR-550, and miR-633) that was able to predict prednisone (PRED) response in childhood ALL patients.…”
Section: Leukemiasmentioning
confidence: 99%